Effect of using Austrian pine cones powder as an additive on oil well cement properties. Issue 1 (January 2023) - AL Khalaf, Hani; Kovacsne, Gabriella Federer; Mohammed, Nagham Alhaj; Horvath, Gabor; Docs, Roland
Abstract: There have been many investigations to improve both the physical and mechanical properties of oil well cement using a wide range of materials. Most of these additives are expensive and practically ineffective. In this article, a comprehensive evaluation was conducted for using Austrian pinecones powder (APCP) as an inexpensive supplementary cementing material (SCM) for well cement. Firstly, Portland cement class G was characterized based on X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD). In this paper, the properties of the cement systems include rheological parameters, density, slurry stability (free water test, and sedimentation test), water absorption, porosity, permeability, the volume of fluid loss, pH value, thermogravimetric analysis, and the mechanical characteristics (in terms of compressive strength, tensile strength, flexural strength, and shear strength bond) were investigated in details. The cement sample containing the APCP was also examined using scanning electron microscopy (SEM). According to the experimental results, adding APCP led to increasing in rheological parameters. Also, led to decreasing in fluid loss, free water, sedimentation effect, and density which positively affects the preservation of the original properties of cement slurry. The results also showed a decrease in the permeability of cement samples and an increase in the porosity and the ability to absorb water. The addition of APCP did not significantly affect the pH values. The addition of APCP also deteriorated the mechanical properties of the cement samples. The addition of the APCP has contributed to an increase in total weight loss at high temperatures. So, the APCP can be considered as a new filler for well cement due to its ability to fill the pores in the cement matrix and at the same time improve some properties of the well cement such as density, free water, sedimentation, and fluid loss.